Incidence, Time Course, and Implications of Electrode Abnormalities in Pediatric Cochlear Implant Recipients. - Harris, Jennifer M.; Neault, Marilyn W.; O’Neill, Elizabeth E.; Griffin, Amanda M.; Kawai, Kosuke; Kenna, Margaret A.; Licameli, Greg R.; O'Neill, Elizabeth E (Ear & Hearing (01960202))
Objectives: To identify the incidence of specific abnormal impedance patterns or electrode faults, and determine their implication and significance, in a pediatric population of cochlear implant recipients.Design: Nine hundred fifty-six cochlear implant devices (621 recipients) were included in this retrospective study. Devices were included if the implantation surgery was performed at our tertiary care hospital, and the recipient was 21 years of age or younger at the time the device was implanted. Device models incapable of producing impedance measures by telemetry were excluded from the study. Individual devices with abnormal impedance measures indicating an open circuit (OC), short circuit (SC), or partial short circuit (partial SC) were included in the study, unless these abnormalities occurred only in the OR and not postoperatively. Device and patient characteristics were examined to determine their relationship to increased incidence of electrode faults or atypical patterns.Results: The incidence of software-identified electrode faults in our exclusively pediatric population was similar to that reported in the literature containing mixed-age cohorts. Nine percent of devices experienced at least one OC or one pair of SCs. Although higher incidence of these faults was seen in some specific device models, the long-term average of these faults was equivalent across manufacturers. No factors examined in this study increased the likelihood of experiencing a software-identified electrode fault. Within the study period under examination (October 1997 to March 2018), partial SCs (presenting as zig-zag or low-flat impedance patterns) were only observed in Cochlear devices. While the incidence of these partial SC abnormalities (non-software-identified faults) was 6% across all models of Cochlear devices, the CI24RCS experienced the highest incidence of partial SCs. The incidence of this pattern was lower in models manufactured after CI24RCS.Conclusions: This study provides incidence of various cochlear implant electrode impedance abnormalities across a large cohort of pediatric recipients. The incidence of all electrode abnormalities was relatively low, particularly partial SCs, which are less well recognized and not currently identified by clinician-accessible software. Incidence of software-identified electrode faults (i.e., SCs and OCs) in our pediatric-only study is similar to the incidence reported in other mixed-population and adult-only studies. These common electrode faults generally are not associated with device failure, and clinicians should feel comfortable reassuring families that an individual electrode fault does not imply an impending device failure. Conversely, those atypical impedance patterns not currently flagged by the programming software as abnormal, but visible to the clinician's eye (i.e., partial SCs in zig-zag or low-flat patterns), have a higher likelihood of device damage and failure. Performance in patients with electrode arrays exhibiting these atypical patterns should be closely monitored for any functional decrement, and proactively managed to maintain performance whenever possible.